Raymond Aron and liberal thought in the twentieth century - Stewart, Iain, 1979- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"Raymond Aron is widely regarded as the most important figure in the history of twentieth-century French liberalism. Yet his status within the history of liberal thought has been more often proclaimed than explained. Though he is frequently lauded as the inheritor of France's liberal tradition, Aron's formative influences were mostly non-French and often radically anti-liberal thinkers. This book explains how, why, and with what consequences he belatedly defined and aligned himself with a French liberal tradition. It also situates Aron within the larger histories of Cold War liberalism and decolonization, re-evaluating his contribution to debates over totalitarianism, the end of ideology, and the Algerian War. By exposing the enduring importance of Aron's student political engagements for the development of his thought, Iain Stewart challenges the prevailing view of Aron's early intellectual trajectory as a journey from naïve socialist idealism to mature liberal realism, offering a new critical perspective on one of the twentieth century's most influential intellectuals"
Introduction: Intellectual politics and the crisis of democracy -- History and politics -- Antitotalitarianism -- The end of ideology -- Raymond Aron and the French liberal tradition -- Raymond Aron and the liberal moment in late twentieth-century French thought.
Includes bibliographical references (pages 246-285) and index.
Keywords: Aron, Raymond, -- 1905-1983.; Political science -- Philosophy -- History -- 20th century; Liberalism -- France -- History -- 20th century; France -- Intellectual life -- 20th century